Cognitive symptoms in early postmenopausal women: Relationship to brain structure: Neuroimaging / Optimal neuroimaging measures for early detection. (7th December 2020) - Newhouse, Paul A.; Conley, Alexander C.; Albert, Kimberly; McDonald, Brenna C.; Saykin, Andrew J.; Boyd, Brian; Kim, Shin‐Gyeom; Dumas, Julie
Abstract: Background: Menopause is associated with increasing cognitive complaints and older women are at increased risk of developing Alzheimer's disease (AD) compared to men. One proposed reason for this reduced cognitive performance is the loss of estrogen following the menopause transition. However, there is difficulty in delineating effects of age and estrogen loss in samples of aging women. The aim of this study was to identify whether in sample of younger postmenopausal women, the level of menopause‐associated cognitive complaints (mCC) was associated with changes in gray‐matter volume and objective cognitive performance. We hypothesized that higher endorsement of cognitive complaints would be associated with smaller gray matter volume in the medial temporal lobe. Additionally, we examined whether the number of endorsed vasomotor, somatic, and mood symptoms was related to cortical gray matter volume. Method: 44 early postmenopausal women (aged 50‐60 years) with differing levels of mCC completed subjective measures of cognitive complaints and postmenopausal symptoms as well as cognitive performance tests of verbal episodic and working memory and completed a structural MRI scan. VBM analysis was performed using the SPM12 package in combination with Matlab 2017b. To assess the effect of mCC on gray‐matter volume, a linear regression model in SPM12 with CCI score as the continuous between‐subject's factor was run. Result: Cognitive complaints were significantly associated with lower gray‐matter volume in the right medial temporal lobe. Increased depressive symptoms and somatic complaints were also significantly related to increased cognitive complaints and smaller medial temporal volumes, however the somatic complaints did not mediate the relationship between cognitive complaints and gray‐matter volume. There was no association between objective performance on the memory tasks and subjective cognitive ratings, or gray‐matter volume. Conclusion: The findings of the present study identify a relationship between the number of endorsed mCC and structural brain differences in younger postmenopausal women. Cognitive complaints but not cognitive performance was associated with lower gray‐matter volume in the right medial temporal lobe. The development of significant menopause‐related cognitive symptoms may represent early brain morphologic and functional changes that may indicate increased risk for cognitive decline.